Depression, Anxiety, and Behavioural Changes during the COVID-19 Pandemic among Medical and Nursing Students - Siti Roshaidai Mohd Arifin; Siti Mardhiah Saiful Azmi; Khadijah Hasanah Abang Abdullah; Nurul Ain Hidayah Abas; Rohayah Husain; Edre M. Aidid; Karimah Hanim Abd Aziz; Ramli Musa; Fathima Begum Syed Mohideen; Asma Perveen; Khairi Che Mat; Izazol Idris (Tech Science Press, 2024)
Indexed by WOS/SCOPUS/ERA